Risk, return and international portfolio analysis: Entropy and linear belief functions - Apiwat Ayusuk (2018)
© Springer International Publishing Switzerland 2015. In this study, we analyze the international portfolio with respect to risk and return aspects.We applied entropy methods to find the optimal portfolio weights. In this method, we used entropy as the objective function and we also compared our results with the conventional method. Moreover, we use the linear belief function to build a portfolio, which can represent market information and financial knowledge and then we usematrix sweepings to integrate the knowledge for evaluating portfolio performance. Overall, our empirical analysis indicates that all entropy methods performed better than Markowitz method, and the finding also suggests that the investor should take the benefit from ASEAN market.